2018
DOI: 10.1021/acs.langmuir.7b03851
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Antiwear Property Under High Pressure of Synthetic Oil-Soluble Ultrathin MoS2 Sheets as Lubricant Additives

Abstract: Wear occurs between two rubbing surfaces. Severe wear due to seizure under high pressure leads to catastrophic failures of mechanical systems and raises wide concerns. In this paper, a kind of synthetic oil-soluble ultrathin MoS sheets is synthesized and investigated as lubricant additives between steel surfaces. It is found that, with the ultrathin MoS sheets, the wear can be controlled under the nominal pressure of about 1 GPa, whereas the bearable nominal pressure for traditional lubricants is only a few hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 28 publications
(37 reference statements)
0
25
0
Order By: Relevance
“…At the same time, the nanocomposites significantly improve the lubricating properties of the base oil due to the synergistic lubrication between LDH and GO or MoS 2 . Chen et al [154] successfully prepared a synthetic oil-soluble ultra-thin MoS 2 sheet as lubricant additive and investigated the wear behavior under about 1 GPa pressure. Because of the uniform dispersion of molybdenum disulfide, wear can be controlled as long as the actual pressure is less than the fracture strength of MoS 2 .…”
Section: Inorganic Additivementioning
confidence: 99%
“…At the same time, the nanocomposites significantly improve the lubricating properties of the base oil due to the synergistic lubrication between LDH and GO or MoS 2 . Chen et al [154] successfully prepared a synthetic oil-soluble ultra-thin MoS 2 sheet as lubricant additive and investigated the wear behavior under about 1 GPa pressure. Because of the uniform dispersion of molybdenum disulfide, wear can be controlled as long as the actual pressure is less than the fracture strength of MoS 2 .…”
Section: Inorganic Additivementioning
confidence: 99%
“…The tribological applications of metals or alloys are usually associated with oil lubrications [234][235][236][237][238][239][240]; thus, studies on the effect of humidity on friction and wear behaviors of metallic substrates are conducted less extensively. Most research focuses on steel interfaces.…”
Section: Metalsmentioning
confidence: 99%
“…17 Meanwhile, it has been reported that ultrathin MoS 2 could significantly improve the lubrication property of oils, as they could be penetrated into the contact area easily. 18,19 In view of the above, it is highly desired to fabricate MoS 2 nanosheets with ultrathin shape and structure defects to apply as oil additives.…”
Section: Introductionmentioning
confidence: 99%